The Use of Jargons of Clash of Clans Game by Makassarese Teenagers - Yudhi Faizal Eka Putra; Serliah Nur; Rabiatul Adawiah; Nurfitrah Nurfitrah (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
Online Games are popular for Indonesian teenagers, and one of them is the Clash of Clans (COC). Each online game has specific terms. Those are known as jargon. This study is aimed to find jargons of Clash of Clans used by teenagers. It is qualitative research using a descriptive method. The result shows that there are seventeen jargons used by three teenagers. They are Archer Troops, Barbarian Troops, Wall Level 3, Wall Level 1, Town Hall 3 Starts, Mortar, Golem, Hogs, Wars, Builder, Hidden Tesla, Clan Castle, Giant, Healer, and Elixir. Those jargons are used in other contexts, out of that online game. the players use this jargon language by considering the things in real life with all of the things in Clash of Clans. So the jargon language from the game is accidentally said by teenagers in their real-life context.